Qualitative comparison of north-american procedures for areawide pedestrian travel measurement - Greene-Roesel, Ryan; Chagas Diógenes, Mara; R. Ragland, David; Lindau, Luis Antonio (Transportes, 2007)
There is no standard system for estimating area-wide pedestrian volumes in the United States. As a result, pedestrian volumes cannot be routinely used to guide transportation investments and monitoring measures performance. Vehicle volumes, by contrast, are measured systematically in each state and are reported to the Federal Highway Administration annually to be used in the allocation of federal funds. This paper investigates the advantages and disadvantages of three approaches to the creation of a standard system of pedestrian volume measurement: direct sampling, survey methods, and modeling. Examples of each method are given, and the potential of each to become a national standard is discussed. Of the three approaches, the modeling methods were judged to be most suitable for tracking pedestrian volumes at the national, state, and sub-state level. A standardized pedestrian volume modeling method could make use of existing data sources without generating the need for a new national pedestrian data collection effort.